Serotonin metabolism in cystic fibrosis. - Partington, M W (1977)
The average blood serotonin level of 67 children with cystic fibrosis was found to be about twice that of age-matched normal children. There was no corresponding increase in the urinary excretion of 5-hydroxyindoleacetic acid (5-HIAA). Children with cystic fibrosis were well able to metabolize serotonin taken by mouth. No significant correlations were found between the blood serotonin level and the platelet count, height, weight, skinfold thickness, and pulmonary function test, 5 out of 44 patients had raised serum IgE levels, and their mean blood serotonin was higher than in those with normal IgE levels. No explanation for this emerged. Comparable findings (raised blood serotonin normal platelet count, normal urinary 5-HIAA) have been reported only in severe mental retardation. Further study of this phenomenon is warranted because (a) a raised blood serotonin level is sufficiently characteristic of cystic fibrosis to explore its use in diagnosis, and (b) it may help to explain the pathogenesis of cystic fibrosis and (c) the metabolism and function of serotonin.